McNally's Puzzle - Sanders, Lawrence (New York Berkley Books, 1997)
Palm Beach private detective Archy McNally is hired by the wealthy owner of a bird store to investigate threats against his life, but the case soon becomes complicated by the murder of McNally's client and the kidnapping-killings of two store clerks.
Keywords: Private investigators -- Florida--Palm Beach -- Murder